2018
DOI: 10.1177/1538574418813746
|View full text |Cite
|
Sign up to set email alerts
|

Amputation-Free Survival in Patients With Diabetes Mellitus and Peripheral Arterial Disease With Heel Ulcer: Open Versus Endovascular Surgery

Abstract: Background: Heel ulcers in patients with diabetes mellitus (DM) and peripheral arterial disease (PAD) are hard to heal. The aim of the present study was to evaluate the difference in amputation-free survival (AFS) between open and endovascular revascularization in patients with DM, PAD, and heel ulcers. Methods: Retrospective comparative study of results of open versus endovascular surgery in patients with DM, PAD, and heel ulcer presented at the multidisciplinary diabetes foot clinic between 1983 and 2013. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In this study, we found approximately 20% of patients with heel ulcers, among the whole population, higher than in similar studies. 2-7,11,12 In our cohort of patients with heel ulcers, we reported 60% of healing without amputation, 20% major amputation, and 20% mortality without healing. The outcomes were significantly worse than for patients without heel ulcers, reinforcing the fact that wound location (specifically the heel) could be a variable influencing the possibility of limb salvage.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In this study, we found approximately 20% of patients with heel ulcers, among the whole population, higher than in similar studies. 2-7,11,12 In our cohort of patients with heel ulcers, we reported 60% of healing without amputation, 20% major amputation, and 20% mortality without healing. The outcomes were significantly worse than for patients without heel ulcers, reinforcing the fact that wound location (specifically the heel) could be a variable influencing the possibility of limb salvage.…”
Section: Discussionmentioning
confidence: 74%
“…The rate of healing reported in previous scientific papers vary between different studies (from 50% to 90%), and in studies where healing time is considered, it is reported that the healing time was between 10 and 33 weeks. 3,7,12-16 The study groups are often not homogeneous due to the number of patients included and the characteristics of DFUs (neuropathic, ischemic, and neuroischemic), whereas our patient cohort consisted only of ischemic patients with several comorbidities that are very hard to manage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, increased oxidative stress and endothelial dysfunction could also explain the high restenosis rates in diabetics undergoing percutaneous transluminal angioplasty [45]. Therefore, as DM contributes to restenosis after percutaneous transluminal interventions [46,47], management of PAD with surgical bypass could be considered more durable [10,48].…”
mentioning
confidence: 99%